If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5t + 9 = 3 + 8t Reorder the terms: 9 + 5t = 3 + 8t Solving 9 + 5t = 3 + 8t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-8t' to each side of the equation. 9 + 5t + -8t = 3 + 8t + -8t Combine like terms: 5t + -8t = -3t 9 + -3t = 3 + 8t + -8t Combine like terms: 8t + -8t = 0 9 + -3t = 3 + 0 9 + -3t = 3 Add '-9' to each side of the equation. 9 + -9 + -3t = 3 + -9 Combine like terms: 9 + -9 = 0 0 + -3t = 3 + -9 -3t = 3 + -9 Combine like terms: 3 + -9 = -6 -3t = -6 Divide each side by '-3'. t = 2 Simplifying t = 2
| (19.2)(10)(3.14)= | | 4x+2=5-2x | | 4(x+2)+3x=6 | | 3(x+3)+11=2(x+3) | | 6+r=12 | | Ln(x-1)+ln(x)=ln(x+8) | | 2x=2(x+90) | | 2-x=2x | | Y=14x+12 | | 2(3x-4)+5=9 | | 5x+12-4x-15=30 | | 9x=5(x+48) | | 23+666=2t | | 4p+9q+5p+3q= | | 15x+20y=180 | | 3(x-17)+4=1 | | 7x+4y=7.5 | | 3.6r=-72 | | =2x-3(4x-6) | | 10x=8(x+12) | | 116=16x-4x^2 | | 30=-5+7x | | p^2-1p-18=2 | | 8w=4640 | | 9h=21+6h | | 36n-4n^2=0 | | -2.8(y-1.3)=18.76 | | b+6.4=-12.13 | | 5u+1=3y+13 | | v=3rh | | 5x+3x+18=180 | | x(8-2x)(11-2x)=0 |